Numbers Games: Undercounting Unemployment and its Consequences. - Shriberg, Amy Burke (Dissent (00123846))
The unemployment figures produced by the U.S. Bureau of Labor Statistics reflect a narrow definition of unemployment. Many Americans are excluded from these figures, and the result obscures the necessary debate about the overall health of the nation's economy and its ability to provide all citizens with decent and family-supporting jobs. If more of the country's citizens understood the true rate of unemployment and how it is measured, support for a permanent public jobs program could emerge, and liberals might be able to restart discussions about a full-employment agenda.